(untitled) (Ameghiniana, 2013)
"In this paper the author describes several specimens of Rhacopteris szajnochai Kurtz, validating the name at the same time. The materials are found in Upper Carboniferous strata of the Jejenes Formation, San Juan Province. It is also suggested that the name Rhacopteris salamandra Kurtz, used in palaeofloristic lists, should be abandoned because the material corresponds to the same species, a basal part of a frond."